COMPOSIÇÃO FÍSICO-QUÍMICA DE MÉIS PRODUZIDOS E COMERCIALIZADOS NO MUNICÍPIO DE SANTA ROSA – RS - Vicenzi, Raul; Soares, José M.; Ferreira, Débora B.; Welke, Juliane E.; Teixeira, Marina S.; Reginatto, Sabrina; Kleinubing, Aline L. R. (Salão do Conhecimento, 2013)
Resumo